Role of sublingual asenapine in treatment of schizophrenia - Citrome L (Dove Medical Press, 2011)
Leslie CitromeNew York University School of Medicine, Department of Psychiatry, New York, NY, USAAbstract: Asenapine tablets are a new option for the treatment of schizophrenia. Sublingual administration is essential because bioavailability if ingested is less than 2%. Efficacy is supported by acute and long-term randomized controlled studies conducted by the manufacturer, with asenapine 5 mg twice daily evidencing superiority over placebo in six-week studies of acute schizophrenia, and flexibly-dosed asenapine (modal dose 10 mg twice daily) superior to placebo in a 26-week maintenance of response study. Tolerability advantages over some second-generation antipsychotics, such as olanzapine, include a relatively favorable weight and metabolic profile, as demonstrated in a 52-week randomized, head-to-head, double-blind clinical trial. Although dose-related extrapyramidal symptoms and akathisia can be present, the frequency of these effects is lower than that for haloperidol and risperidone. Somnolence may also occur, and appears to be somewhat dose-dependent when examining rates of this among patients receiving asenapine for schizophrenia and bipolar disorder. Prolactin elevation can occur, but at a rate lower than that observed for haloperidol or risperidone. Unique to asenapine is the possibility of oral hypoesthesia, occurring in about 5% of participants in the clinical trials. Obstacles to the use of asenapine are the recommendations for twice-daily dosing and the need to avoid food or liquids for 10 minutes after administration, although the bioavailability is only minimally reduced if food or liquids are avoided for only two minutes.Keywords: antipsychotic, asenapine, clinical trials, schizophrenia